Isolation, Molecular Characterization and Probiotic Potential of Lactic Acid Bacteria in Saudi Raw and Fermented Milk. (25th July 2018) - Bin Masalam, Maged S.; Bahieldin, Ahmed; Alharbi, Mona G.; Al-Masaudi, Saad; Al-Jaouni, Soad K.; Harakeh, Steve M.; Al-Hindi, Rashad R.
Abstract : Probiotic bacteria can confer health benefits to the human gastrointestinal tract. Lactic acid bacteria (LAB) are candidate probiotic bacteria that are widely distributed in nature and can be used in the food industry. The objective of this study is to isolate and characterize LAB present in raw and fermented milk in Saudi Arabia. Ninety-three suspected LAB were isolated from thirteen different types of raw and fermented milk from indigenous animals in Saudi Arabia. The identification of forty-six selected LAB strains and their genetic relatedness was performed based on 16S rDNA gene sequence comparisons. None of the strains exhibited resistance to clinically relevant antibiotics or had any undesirable hemolytic activity, but they differed in their other probiotic characteristics, that is, tolerance to acidic pH, resistance to bile, and antibacterial activity. In conclusion, the isolates Lactobacillus casei MSJ1, Lactobacillus casei Dwan5, Lactobacillus plantarum EyLan2, and Enterococcus faecium Gail-BawZir8 are most likely the best with probiotic potentials. We speculate that studying the synergistic effects of bacterial combinations might result in a more effective probiotic potential. We suspect that raw and fermented milk products from animals in Saudi Arabia, especially Laban made from camel milk, are rich in LAB and have promising probiotic potential.